(untitled) (Modern education and development, 2024)
Motivation is a critical factor in the success of language learning, influencing learners’ persistence, engagement, and overall achievement. This article explores effective strategies for fostering motivation in language learners, emphasizing both intrinsic and extrinsic motivation. Key approaches include setting clear, achievable goals, providing a supportive learning environment, promoting autonomy, and incorporating cultural relevance into the learning process. Additionally, the importance of creating a sense of progress, encouraging a growth mindset, and leveraging technology is discussed. By understanding and applying these strategies, educators and learners can sustain motivation, leading to more effective and enjoyable language acquisition.